2001
DOI: 10.1109/36.974992
|View full text |Cite
|
Sign up to set email alerts
|

PIn. I. An operational nonlinear physical inversion algorithm for precipitable and cloud liquid water estimate in nonraining conditions over sea

Abstract: An operational nonlinear Physical Inversion (PIn) algorithm for precipitable and cloud liquid water estimate is described. It is suited for a generic conical scanning satellite microwave radiometer acquisitions over sea, in non-raining conditions. The algorithm does not need any calibration phase, and is independent from the availability of in-situ data, being consistent in different geographical and climatological situations. Adopted formulation is addressed to provide observational data to help validating wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2004
2004

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Equations (2) and (3) are the corrected retrieval models, utilising a two and a three-channel approach, respectively. The authors reported a reduced estimated standard error equal to 1.5 kg/m 2 for equation (2) and to 1.45 kg/m 2 for equation (3).…”
Section: A Ssm/i Pw Statistical Algorithmsmentioning
confidence: 96%
See 2 more Smart Citations
“…Equations (2) and (3) are the corrected retrieval models, utilising a two and a three-channel approach, respectively. The authors reported a reduced estimated standard error equal to 1.5 kg/m 2 for equation (2) and to 1.45 kg/m 2 for equation (3).…”
Section: A Ssm/i Pw Statistical Algorithmsmentioning
confidence: 96%
“…Starting from a new developed fast nonlinear physical inversion algorithm [3] an operative procedure has been developed in order to estimate atmosphere parameters over the Mediterranean basin. The main design parameters of the procedure were speed and flexibility.…”
Section: Operative Pin Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The inversion module solves a direct model equation (carried out from the utilised forward model) by means of an inversion model. 1 This module is supplied with a first guess of parameters to be retrieved, and satellite measured brightness temperatures of an entire satellite scene. 2 For the entire scene, the following parameter images are generated:…”
Section: Pin Operative Proceduresmentioning
confidence: 99%
“…1 Starting from such technique, an operative Procedure (named PIn, for Physical Inversion) has been developed and assessed to estimate integrated precipitable water vapour along with liquid water path and water vapour effective profile, utilising both the SSM/I and TMI radiometers. 2 The consistency of water vapour (WV) and liquid water path (LWP), estimated from both radiometers was examined, utilising a fast nonlinear physical inversion scheme developed for this purpose.…”
Section: Introductionmentioning
confidence: 99%